2005
DOI: 10.1002/ca.20250
|View full text |Cite
|
Sign up to set email alerts
|

Design characteristics that affect speed of information access and clarity of presentation in an electronic neuroanatomy atlas

Abstract: Functional Neuroanatomy, an interactive electronic neuroanatomical atlas, was designed for first year medical students. Medical students have much to learn in a limited time; therefore a major goal in the atlas design was that it facilitate rapid, accurate information retrieval. To assess this feature, we designed a testing scenario in which students who had never taken a neuroanatomy course were asked to complete two equivalent tests, one using the electronic atlas and one using a comparable hard copy atlas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Our results highlight a positive learning gain. The results are in line with the previous studies which have also documented an increase in the neuroanatomy knowledge of the learner-cohorts, when testing the efficacy of their respective neuroanatomy e-learning tools ( Stewart, Nathan and Nyhof-Young, 2007 ; Nowinski et al , 2009 ; Adams and Wilson, 2011 ; Chariker, Naaz and Pani, 2011 ; Ruisoto et al , 2012 ; Li et al , 2014 ; Palomera, Mendez and Galino, 2014 ; Drapkin et al , 2015 ; L. K. Allen, Eagleson and de Ribaupierre, 2016 ; de Faria et al , 2016 ; Cui et al , 2017 ). In our study, the fact that all three groups performed similarly on the baseline quiz (quiz 1) and all improved significantly on quiz 2, could be better understood by interpreting the results in the overall context of the academic course.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results highlight a positive learning gain. The results are in line with the previous studies which have also documented an increase in the neuroanatomy knowledge of the learner-cohorts, when testing the efficacy of their respective neuroanatomy e-learning tools ( Stewart, Nathan and Nyhof-Young, 2007 ; Nowinski et al , 2009 ; Adams and Wilson, 2011 ; Chariker, Naaz and Pani, 2011 ; Ruisoto et al , 2012 ; Li et al , 2014 ; Palomera, Mendez and Galino, 2014 ; Drapkin et al , 2015 ; L. K. Allen, Eagleson and de Ribaupierre, 2016 ; de Faria et al , 2016 ; Cui et al , 2017 ). In our study, the fact that all three groups performed similarly on the baseline quiz (quiz 1) and all improved significantly on quiz 2, could be better understood by interpreting the results in the overall context of the academic course.…”
Section: Discussionsupporting
confidence: 91%
“…In the past, several neuroanatomy learning tools have been developed and / or evaluated for their educational efficacy ( Stewart, Nathan and Nyhof-Young, 2007 ; Nowinski et al , 2009 ; Adams and Wilson, 2011 ; Chariker, Naaz and Pani, 2011 ; Ruisoto et al , 2012 ; Li et al , 2014 ; Palomera, Mendez and Galino, 2014 ; Drapkin et al , 2015 ; L. K. Allen, Eagleson and de Ribaupierre, 2016 ; de Faria et al , 2016 ; Cui et al , 2017 ). Although, these studies have reported enhanced learners’ knowledge of neuroanatomy, none have documented the theoretical underpinnings and the conceptual framework which informed the pedagogical design of these e-learning tools, thus raising queries with regards to their instructional design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation